2005
DOI: 10.1185/030079904x20303
|View full text |Cite
|
Sign up to set email alerts
|

Costs of attention deficit–hyperactivity disorder (ADHD) in the US: excess costs of persons with ADHD and their family members in 2000

Abstract: The annual cost of ADHD in the US is substantial. Both treated and untreated persons with ADHD, as well as their family members, impose consider able economic burdens on the healthcare system as a result of this condition. While these first estimates of the cost of ADHD to the nation are suggestive of its substantial economic burden, future research needs to refine and build on this analysis, particularly in the context of a model to control for related co-morbidities. Similarly, since these results are based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
153
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(162 citation statements)
references
References 35 publications
6
153
0
3
Order By: Relevance
“…ADHD is associated with broad impairment in many Health Related Quality of Life (HRQoL) parameters, including academic performance, behaviour at school, peer relations and family function [5]. Studies have indicated that, compared to their peers without ADHD, young people with ADHD also exhibit higher levels of comorbidity with other psychiatric disorders as oppositional defiant disorder, conduct disorder, anxiety disorder and depression, and with somatic conditions as asthma [2]. Furthermore, they have an increased risk of accidents and severe injury [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ADHD is associated with broad impairment in many Health Related Quality of Life (HRQoL) parameters, including academic performance, behaviour at school, peer relations and family function [5]. Studies have indicated that, compared to their peers without ADHD, young people with ADHD also exhibit higher levels of comorbidity with other psychiatric disorders as oppositional defiant disorder, conduct disorder, anxiety disorder and depression, and with somatic conditions as asthma [2]. Furthermore, they have an increased risk of accidents and severe injury [2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that, compared to their peers without ADHD, young people with ADHD also exhibit higher levels of comorbidity with other psychiatric disorders as oppositional defiant disorder, conduct disorder, anxiety disorder and depression, and with somatic conditions as asthma [2]. Furthermore, they have an increased risk of accidents and severe injury [2]. ADHD may also affect the health and ability to work of family members [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The estimated burden of ADHD in the United States was $31.6 billion in 2000, and 45% of that burden was attributable to excess health carec osts of family members of patients with ADHD. 11 Compared with am atched cohort, ADHD patients had almost 3t imes greater annual health carec osts, and family members had approximately 1.9 times higher annual health caree xpenditures compared with am atched cohort of family members of non-ADHD patients. 12 ADHD in adults is amenable to treatment and is best controlled by ac ombination of medications and psychosocial interventions.…”
Section: What This Study Addsmentioning
confidence: 99%
“…38 Providing oxygen to children with bronchiolitis, stimulants to students with attention or hyperactivity problems, and phototherapy to infants with elevated bilirubin values are unlikely to be included in waste estimates, despite the fact that in some cases these interventions are not beneficial. The annual US health care costs for each of these conditions are $543 million, 39 $1.6 billion, 40 and $150 million, 20 respectively.…”
Section: Financial Strainmentioning
confidence: 99%